Combat Pair The Evolution of Air Force-Navy Integration in Strike Warfare - Lambeth, Benjamin S. (RAND Corporation, 2007)
This report documents the exceptional cross-service harmony that the U.S. Air Force and U.S. Navy have steadily developed in their conduct of integrated strike operations since the first Persian Gulf War in 1991. That close harmony contrasts sharply with the situation that prevailed throughout most of the Cold War, when the two services maintained separate and unique operating mindsets and lacked any significant interoperability features.